Pemberdayaan Masyarakat Di Kampung Pinang Sebatang Kecamatan Tualang Kabupaten Siak - Surya Daliati; Herniwati Herniwati; Sudaryanto Sudaryanto (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
Pinang Sebatang Village, Tualang District, Siak Regency comes from various different areas, where the majority of the population is the most dominant ethnic Malay. The problems that exist in this village include poor people. To overcome this, community service was carried out by means of online implementation methods and discussion and assistance. As a result, community empowerment went well and there was support from the local government in the form of budget allocations for annual activities for community empowerment. Like in 2019, IDR 97,057,000, only IDR 39,761,000 can be used. This means that there is an excess of budget use of IDR 57,296,000 from the total village budget of IDR 2,418,213,189. With this amount, it is still not able to solve various problems that exist in society. The remaining surplus from the previous year's budget was Rp 69,403,223 and the remaining excess of the current year's use was Rp 303,971,406. So the village / village spending in 2019 will be IDR 2,021,145,005. This empowerment activity needs to be continuously improved by involving the private sector.